"Kmiotek Niebieski" w Wielkopolsce czyli bractwo św. Izydora w Nowym Kramsku w XVII-XIX wieku = "Heavenly Peasant" in Greater Poland, that is the Brotherhood of Saint Isidore in Nowe Kramsko in the 17th-19th centuries - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article entitled: "Heavenly Peasant in Greater Poland, that is the Brotherhood of Saint Isidore in Nowe Kramsko in the 17th-19th Centuries", is devoted to the activity of the religious confraternity in the Polish rural environment. Isidore of Madrid is one of the few saints coming from the peasants. In the 17th and 18th centuries, the cult of Isidore spread in Europe, reaching also Poland.
Keywords: Nowe Kramsko (pow. babimojski); bractwa religijne; św. Izydor Oracz (1079-1172); Religious brotherhood; Saint Isidore